Image-guided surgery in gynecologic oncology. (November 2017) - Azaïs, Henri; Canlorbe, Geoffroy; Kerbage, Yohan; Grabarz, Anne; Collinet, Pierre; Mordon, Serge
Image-guided surgery is a relevant way to reduce surgical morbidity and maximize cytoreductive surgery approach especially in ovarian cancer. Sentinel lymph node detection is a promising approach to avoid radical lymph node dissection and is slightly becoming standard in daily practice in endometrial and cervical cancer surgery even if it needs to be evaluated more precisely. Regarding carcinomatosis of ovarian origin, detection and treatment of microscopic disease could be appropriate to avoid local recurrences. Photodiagnosis and photodynamic therapy are innovative techniques that allow to precise limits of excision (fluorescence-guided surgery) and to treat microscopic disease. Further developments of those strategies are necessary to become standard diagnosis tools and treatment options.